English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-03-02 03:09:29 · 5 answers · asked by Chirag D 1 in Science & Mathematics Mathematics

5 answers

y2+19y-66=0
(y+22)(y-3)=0
y=3 or y=-22

2007-03-02 03:19:02 · answer #1 · answered by kinvadave 5 · 0 0

y2+19y-66=0
(y-3)(y+22)=0
y = 3 or -22

2007-03-02 03:13:45 · answer #2 · answered by jaybee 4 · 0 0

y2+19y-66= 0

(y+22)(y-3)=0

y+22=0
y= -22

and

y-3=0
y=3

2007-03-02 03:14:26 · answer #3 · answered by Anonymous · 0 0

You can factor this into (y-3)(y+22)=0. Now solve y-3=0 ad y+22=0 to get y=3 or y=-22.

Or you can use the quadratic formula to get these answers.

2007-03-02 03:15:10 · answer #4 · answered by MISSYCL 2 · 0 0

y2+19y-66=0?
y2+22y-3y-66=0
y(y+22)-3(y+22)=0
(y+22)(y-3)=0
y=3,y=-22

2007-03-02 03:14:15 · answer #5 · answered by @"..n"..i"..L 2 · 0 0

fedest.com, questions and answers